Correlation of fine needle aspiration cytology with histopathology findings in cases of thyroid lesions in Bir Hospital - Thapa, PB; Shrestha, D; Pradhananga, JP (Journal of College of Medical Sciences-Nepal, 2014)
Aims: To correlate the findings of fine needle aspiration cytology (FNAC) with the histopathology( HPE) of the excised nodule or specimen and to assess the accuracy and efficacy of FNAC in the diagnosis of the thyroid nodules. Materials and methods: This is a prospective study conducted at the Department of Ear Nose Throat (ENT) & Head & NecK Surgery( HNS), National Academy of Medical Sciences, Bir Hospital, Kathmandu from 2nd January 2009 to 29th December 2011. One hundred patients with thyroid nodule were included in the study. Results: Out of 100 patients 77 were females and 23 males. The age ranged from 11-60 years. Statistical analysis of results for Benign Thyroid lesion showed 98.6% sensitivity, 75 % specificity. Likewise, results for Malignant thyroid lesions showed 75 % sensitivity, 98.6 % specificity . Conclusion: FNAC has high accuracy in the diagnostic evaluation of thyroid lesions. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 23-29 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9670